2019
DOI: 10.5343/bms.2019.0010
|View full text |Cite
|
Sign up to set email alerts
|

New record of the encrusting alga Ramicrusta textilis overgrowing corals in the lagoon of Dongsha Atoll, South China Sea

Abstract: The crustose calcareous alga, Ramicrusta textilis Pueschel and G.W. Saunders (Peyssonneliaceae, Rhodophyta), was recently observed to overgrow dead and living corals in shallow lagoon patch reefs of Dongsha Atoll, South China Sea. DNA barcoding revealed that R. textilis frequently co-occurred in a complex with other crustose algae of the family Peyssonneliaceae and the genus Lobophora, forming patchy crusts that cover 3%-29% of the benthic substrate. This is the first record R. textilis overgrowing corals in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…Dixon and Saunders [ 13 ] used 4% K2P COI-5P interspecific variation as a threshold to distinguish Ramicrusta species. Most Ramicrusta species have been reported to exhibit low (< 1.0%) intraspecific sequence divergence values [ 13 , 15 , 19 ], with Ramicrusta appressa K.R.Dixon being the sole exception [ 13 ]. There was an average of 11.97% COI-5P sequence divergence between Ramicrusta species, ranging from 10.24% ( R .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dixon and Saunders [ 13 ] used 4% K2P COI-5P interspecific variation as a threshold to distinguish Ramicrusta species. Most Ramicrusta species have been reported to exhibit low (< 1.0%) intraspecific sequence divergence values [ 13 , 15 , 19 ], with Ramicrusta appressa K.R.Dixon being the sole exception [ 13 ]. There was an average of 11.97% COI-5P sequence divergence between Ramicrusta species, ranging from 10.24% ( R .…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of invariable sites and gamma shape parameters were estimated from the data, and sequence divergence was calculated using the MEGA version X computer software [ 36 ]. Sequence divergence was calculated using a neighbor-joining algorithm under a Kimura 2-parameter substitution model, which has been most often used when describing or reporting new Ramicrusta species [ 13 , 19 , 23 ]. Nonparametric bootstrapping (1000 replicates) was used to estimate node support.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…), have not been extensively studied, and until now, little information is known regarding the taxonomic identity of the species composing the crust, their ecology, or their range distribution 43,68,69 . A recent study in which PAC were observed to be overgrowing corals in the South China Sea revealed that crusts frequently co-occurred in a complex which comprised Ramicrusta textilis, members of the family Peyssonneliaceae and also the genus Lobophora 70 . Peyssonnelid algae often are also only identified to genus, as species share a simple gross morphology (as in 69 ).…”
Section: Discussionmentioning
confidence: 99%